Tensiometer Use In Scheduling Irrigation - Alam, Mahbub; Rogers, Danny H. (My University, 1997)
Tensiometers are soil water measuring devices that are sensitive to soil water change and useful for irrigation scheduling.
L796_1997-07
Keywords: L796; Crops; L